2023
DOI: 10.3390/agronomy13010203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Resistance Mechanisms to Fall Armyworm, Spodoptera frugiperda in Tropical Maize Inbred Lines

Abstract: The fall armyworm (FAW), Spodoptera frugiperda, a pest of maize native to the Americas first reported in West and Central Africa in 2016, severely threatens maize production and food security in Sub-Saharan Africa. Native genetic resistance is one of the best methods of control of insect pests as it is contained in the seed making it more amenable for use by farmers compared to other interventions and it is also compatible with other integrated pest management (IPM) options. An intensive screening against FAW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The 4 d old S. frugiperda larvae preferred the whorl tissue Tx601 (susceptible control) over the Mp708 (resistant) tissue [39], which suggested non-preference (or antixenosis) of Mp708 as one of the possible resistance mechanisms. For multiple insect resistance mechanisms, by examining tropical maize inbred lines CML71, CML125, CML370, and CKSBL10008, with known resistance to multiple stem borers, revealed that CKSBL10008 and CML71 show high level of antibiosis to S. frugiperda [17]. In addition, by using extensive phenotyping data on S. frugiperda injury ratings from 289 maize germplasm lines, seven genes and multiple pathways associated with its feeding damage were identified [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 d old S. frugiperda larvae preferred the whorl tissue Tx601 (susceptible control) over the Mp708 (resistant) tissue [39], which suggested non-preference (or antixenosis) of Mp708 as one of the possible resistance mechanisms. For multiple insect resistance mechanisms, by examining tropical maize inbred lines CML71, CML125, CML370, and CKSBL10008, with known resistance to multiple stem borers, revealed that CKSBL10008 and CML71 show high level of antibiosis to S. frugiperda [17]. In addition, by using extensive phenotyping data on S. frugiperda injury ratings from 289 maize germplasm lines, seven genes and multiple pathways associated with its feeding damage were identified [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous reports suggest a correlation among genes that confer resistance to multiple insects on maize, e.g., genes conferring resistance to foliar-feeding S. frugiperda and the southwestern corn borer, Diatraea grandiosella Dyar (Lepidoptera: Crambidae), and genes conferring resistance to ear-feeding European corn borer, Ostrinia nubilalis (Hübner) (Lepidoptera: Crambidae), and H. zea [2,[14][15][16]. Also, tropical maize inbred lines 'CML71', 'CML125', 'CML370' and 'CKSBL10008', derived from multiple borer resistant inbred lines, demonstrated that CKSBL10008 and CML71 confer high levels of antibiosis to S. frugiperda [17].…”
Section: Introductionmentioning
confidence: 99%